Microrresistência no cotidiano da prática pedagógica docente no curso de graduação em Serviço Social - Silva, Ivonete da (2018)
In this thesis, we start from the assumption that daily micro-resistance, a term forged from the thinking of Michel de Certeau (2013), is a perspective capable of allowing, perceiving and capturing what is happening in social and institutional spaces through tactics silent and subtle ones that act on the dominant system, interfering heavily on their own goals or purposes. It suggests that the author "play the game" through cunning to, within the established order, produce his own resistance and small and great transformations. It is a political action and competence that we will base our argument on the object of this research: the daily practice of teaching pedagogy in the Institutions of Higher Education of the Private Network in the city of São Paulo - IES-RP / SP. Our intention is to analyze the tactics used by teachers inserted in 02 IES-RP / SP, identified active in the Ministry of Education and Culture - MEC between May 2015 and February 2016; to identify the teacher as determining subjects that metaphorize the dominant order, transforming and materializing, albeit in relative independence, their commitment to a quality education, reiterating the project of the profession in opposition to the marketing idea of education. As subjects of this research, we interviewed social assistant teachers who carry out the pedagogical teaching practice at IES / RP-SP, with on-site courses of Undergraduate Social Work. As a methodological approach, we opted for the multidimensional perspective presented by Morin (2013), constructing the method path in the research development process, articulating different correlated knowledge to the object of study, such as Microhistory, presented by Barros (2013) . Among the results, it was possible to identify in the teachers' narratives axioms of continuity, resistances, oppositions, interactions, fruition, creativity in the diagram of cultural exchanges in a hologramatic and recursive movement, conferring to the anonymous spaces new forms of resistance, thus revealed, in the microresistences